Health care services, racial and ethnic minorities and underserved populations patient and provider perspectives - Kronenfeld, Jennie J. (Amsterdam ; Boston : Elsevier JAI, 2005)
The theme of this volume is "Health Care Services, Racial and Ethnic Minorities and Undeserved Populations: Patient and Provider Perspectives". The volume is divided into five sections. The first section discusses the overall issue of health care disparities and undeserved populations and also provides introductory material about the rest of the volume. The next section focuses on issues that relate to gender. The third section provides papers on some other specific examples of undeserved populations: those with mental health concerns, those with concerns related to emotional well being, the elderly population and sex workers.The fourth section includes papers that discuss treatment disparities and providers of care. The final section includes papers that relate to policy concerns. The topic of health care services and undeserved populations is one of growing importance within the US health care system and one of importance in health care systems across the world. Concern about equity in health care is not new. There is a long tradition in medical sociology of studies of inequities in health status and use of health care services. Over the past ten to twenty years, there have been many studies that have documented that race and socioeconomic status (SES) influence the use of health care services.Within the US in the past decade, this area of concern is often described as studies of health disparities and this volume is a contribution to that research. This volume examines the issue more broadly, by including some issues in countries besides the US and examining the role of providers in treatment disparities and important policy concerns.
Health care disparities and underserved populations: issues of social factors / Jennie Jacobs Kronenfeld -- African American teen mothers and reproductive health care services : gender and the context of intention / Sarah Jane Brubaker -- Breast cancer treatment decision making: does the sisterhood of breast cancer transcend culture? / Pamela H. Wescott ... [et al.] -- Social factors, need, and mental health services utilization: findings of the national comorbidity survey / Anthony Kouzis -- Social determinants of health care access among sex industry workers in Canada / Rachel Phillips, Cecilia Benoit -- Presenting and anticipatory needs for accessibility to providers and services : the experiences of six frail older widows living in medically underserved areas / Eileen J. Porter -- Effects of managed health insurance on physical and emotional well-being / D. Clayton Smith, James W. Grimm, Zachary W. Brewster -- 'Nothing happens in medical school that prepares you for working with anyone who's different' : informal learning and socio-clinical knowledge amongst family physicians / Eric Mykhalovskiy, Karen Farrell -- Rapid clinical decisions in context : a theoretical model to understand physicians' decision-making with an application to racial/ethnic treatment disparities / Joshua H. Tamayo-Sarver ... [et al.] -- The impacts of public policy implementation on tribal health care management : the case of OEO/CAP / Michèle Companion -- Health systems and health promotion programs - the necessity of cultural competence: an ethical analysis / Valda Ford, Beth Furlong -- The biomedical legacy in minority health policy-making, 1975-2002 / Drew Halfmann, Jesse Rude, Kim Ebert -- Literac : influence on access and use of the health care system / Karen Seccombe, Richard S. Lockwood, Stephen Reader.
Includes bibliographical references.
Description based on print version record.
Keywords: Discrimination in medical care; Minorities -- Medical care; Health services accessibility; Medical policy; Health systems & services; USA; Medical -- Health Care Delivery